2020
DOI: 10.1210/clinem/dgaa269
|View full text |Cite
|
Sign up to set email alerts
|

Late-Night Salivary Cortisol in Healthy, Community-Dwelling Asian Indians Assessed by Second-Generation ECLIA

Abstract: Background Late-night salivary cortisol (LNSC) is used as a screening test for Cushing syndrome (CS), but there is no community-derived normative data for the normal upper limit in the South Asian population. This study aimed to determine the upper limit of normal (97.5th percentile) for LNSC in an Asian Indian population using a commercially available second-generation electrochemiluminiscence immunoassay (ECLIA). Methods LN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…18,20 We employed a ROC analysis to derive the optimal LNSC cut-off with highest sensitivity and specificity, an approach most consistently used in the literature. 19,[21][22][23][24][25][26][27][28][29][30][31][32] Our ROC-derived LNSC cut-off was also very close to the 95th percentile determined in healthy population by the manufacturer, that is, 7.56 nmol/L 8 and the 97.5th percentile determined in healthy community-dwelling Asian Indians by Prasad et al 35 with the same assay, that is, 6.89 nmol/L. Furthermore, we found that an alternative approach of using 95th percentile of LNSC (6.76 nmol/L) in our controls as the cut-off yielded a similarly high sensitivity (98%) and specificity (96%).…”
Section: Late-night Salivary Cortisol (Lnsc) Performance Using 95th P...supporting
confidence: 83%
See 1 more Smart Citation
“…18,20 We employed a ROC analysis to derive the optimal LNSC cut-off with highest sensitivity and specificity, an approach most consistently used in the literature. 19,[21][22][23][24][25][26][27][28][29][30][31][32] Our ROC-derived LNSC cut-off was also very close to the 95th percentile determined in healthy population by the manufacturer, that is, 7.56 nmol/L 8 and the 97.5th percentile determined in healthy community-dwelling Asian Indians by Prasad et al 35 with the same assay, that is, 6.89 nmol/L. Furthermore, we found that an alternative approach of using 95th percentile of LNSC (6.76 nmol/L) in our controls as the cut-off yielded a similarly high sensitivity (98%) and specificity (96%).…”
Section: Late-night Salivary Cortisol (Lnsc) Performance Using 95th P...supporting
confidence: 83%
“…Since salivary cortisol measurements were not found to be affected by age (in adults <65 years of age) in a recent study by Raff et al, 39 we do not expect a significant implication of this difference for our study findings. Third, we used serum separator tubes (which are routinely available in our hospital) to collect saliva samples rather than the more commonly used plain polypropylene tubes 17,35 . However, the approach was similar in both cases and controls; whether this nonconventional approach affects concentration of cortisol in saliva samples needs a formal evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…3 Late night salivary cortisol is one of the preferred screening tests for Cushing Syndrome with well-defined cut-off values. 2,4 Salivary cortisol performs better than plasma cortisol in conditions with altered cortisol-binding globulin (CBG) levels like contraceptive use, pregnancy and liver cirrhosis. [5][6][7] In spite of the advantages, the role of salivary cortisol in the diagnosis of adrenal insufficiency (AI) is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is stable at room temperature for up to 5 days thus facilitating storage and transportation 3 . Late night salivary cortisol is one of the preferred screening tests for Cushing Syndrome with well‐defined cut‐off values 2,4 . Salivary cortisol performs better than plasma cortisol in conditions with altered cortisol‐binding globulin (CBG) levels like contraceptive use, pregnancy and liver cirrhosis 5–7 .…”
Section: Introductionmentioning
confidence: 99%
“…Electro chemiluminescence immuno assay is a new developing method to determine antibodies in human being's blood sample.this has evolved from various other immunoassay methods that were previously used for detection of enzyme/antibody etc 5 Determination of antibody is done by chemical reactivity with materials like ruthenium, osmium etc., that are coated on monoclonal antibodies and on reaction produce luminescent molecules hence the name. This production of luminescent molecules makes determination uncomplicated 6 .…”
Section: Introductionmentioning
confidence: 99%